2019
DOI: 10.1016/j.newast.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Effective sound speed in relativistic accretion discs around Schwarzschild black holes

Abstract: For low angular momentum axially symmetric accretion flow maintained in hydrostatic equilibrium along the vertical direction, the value of the Mach number at the critical points deviates from unity, resulting in the non-isomorphism of the critical and the sonic points. This introduces several undesirable complexities while analytically dealing with the stationary integral accretion solutions and the corresponding phase portraits. We propose that the introduction of an effective dynamical sound speed may resolv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…It has been recently proposed that accreting astrophysical systems may be considered as natural examples of classical analogue gravity models [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In our present work, we shall consider such a model to manifest our formalism.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently proposed that accreting astrophysical systems may be considered as natural examples of classical analogue gravity models [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In our present work, we shall consider such a model to manifest our formalism.…”
Section: Introductionmentioning
confidence: 99%
“…The present work may also be useful in the context of analogue gravity phenomenon. It has been observed that a curved acoustic metric may be embedded within the accreting matter and such space-time may be generated through the perturbation of accretion flow ( [Ananda et al, 2015], [Bollimpalli et al, 2017], [Shaikh et al, 2017], , [Shaikh, 2018], [Datta et al, 2018], [Shaikh et al, 2019], [Datta and Das, 2019]). The present work will also lead to the understanding of how the flow thickness of axially symmetric accretion in the Kerr metric may influence the properties of the analogue surface gravity of the corresponding sonic space-time.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the fact that accretion of hydrodynamic fluid onto astrophysical black holes are usually transonic in nature ( [Liang and Thomson, 1980]), it has been recently proposed that accreting astrophysical systems may be considered as natural examples of classical analogue gravity models ( [Das, 2004], [Dasgupta et al, 2005], [Abraham et al, 2006], [Das et al, 2007], [Pu et al, 2012], [Bilić et al, 2014], [Tarafdar and Das, 2015], [Ananda et al, 2015], [Saha et al, 2016], [Bollimpalli et al, 2017], [Shaikh et al, 2017], [Tarafdar and Das, 2018], , [Shaikh, 2018], [Datta et al, 2018], [Shaikh et al, 2019], [Datta and Das, 2019]).…”
Section: Introductionmentioning
confidence: 99%